Group cognitive behavioral therapy for aggression, self-control, and social support among first grade university students of China - Li, Yutong; Ahmad, Nor Aniza; Omar, Zoharah; Roslan, Samsilah (Melbourne Scientific Publishers, 2018)
The objective of this study was to determine the intervention effect of group cognitive behavioral therapy (G-CBT) for aggression, selfcontrol, and social support among first grade university students of China. This research was a randomized pre- and post-test with control group design. Through stratified random sampling, 1,469 first grade university students, age from 18- to 19-year-old, were obtained. The participants whose score achieved aggressive evaluation standard were selected, and in a random way, 60 subjects were averagely divided into two schemes - G-CBT and the control group. The subjects of G-CBT received 16 sessions of treatment, while subjects in the control group did not receive any intervention. All subjects completed the assessment for 3 times: Pre-test (1 week before intervention), post-test 1 (1 week after intervention), and post-test 2 (4 months after intervention). The results showed that the total score and the scores of all subscales of aggression had dropped significantly (P < 0.05); the total score and the scores of subjective support and utilization degree of social support had increased significantly (P < 0.05); the total score of self-control did not change statistically significant (P > 0.05). Therefore, the G-CBT was effective in treating aggression and the effect was stable; the G-IPT was effective in improving social support, but the effect was not stable; and the self-control level of G-CBT group improved but did not reach significance degree in this study.